FORECASTS OF INCOME AND EXPENSES OF THE STATE TRUST FUNDS AND THE RECONSTRUCTION AND DEVELOPMENT FUND OF THE REPUBLIC OF UZBEKISTAN FOR 2025-2027 - Olimova Guli Bobomurodovna (Ecomind Press, 2025)
This article presents the projected revenues and expenditures of the State Trust Funds and the Reconstruction and Development Fund of the Republic of Uzbekistan for the period 2025–2027. In 2025, the revenues of the State Trust Funds (excluding transfers to the state budget) are forecasted at 66.5 trillion UZS, while expenditures (excluding budget transfers) are expected to reach 62.9 trillion UZS. The share of trust funds in the consolidated budget is projected to decrease in 2026 and 2027.
Keywords: Consolidated budget, transfers, pension fund, employment assistance fund, budget balance, vocational training.